3D Metaphotonic Nanostructures with Intrinsic Chirality - Qiu, Meng; Zhang, Lei; Tang, Zhixiang; Jin, Wei; Qiu, Cheng‐Wei; Lei, Dang Yuan (Advanced functional materials, 2018)
Chirality is a universal geometric property in both micro‐ and macroworlds. Recently, optical chiral effects have drawn increased attention due to their great potential in fundamental studies and practical applications. Significantly, the optical chiral response of artificial structures can be enhanced by orders of magnitude compared to that of their naturally occurring counterparts. These man‐made structures generally exhibit two types of optical chirality: extrinsic chirality and intrinsic chirality. The former relies on external illumination conditions, while the latter arises from the geometric characteristics of 3D objects. Herein, this review mainly focuses on the intrinsic chirality of artificial structures and discusses the existing realizations based on their design principles. In particular, an overview is given of the recent demonstrations of nonlinear optical effects in chiral structures and active chiral structures. Lastly, some promising prospects for future studies in the field are outlined. 3D metaphotonic structures with intrinsic chirality support both optical rotation and circular dichroism, which are orders of magnitude higher than that of their naturally occurring counterparts. They have drawn increased attention due to their potential in fundamental studies in physics, chemistry and biology, and in practical applications, such as negative refractive index media, molecule sensors, and modulators.